Compliance tracking system for training element of OSHA process safety management - N., Azmi; Hanida, Abdul Aziz (2018)
There are many accidents happen in process industries such as in a chemical plant that killed peoples’ life. One of the contributing factors of accidents happen is because of inadequate training provided to employees especially in operational. One of the establish standard that highlighted this issue is training element of OSHA Process Safety Management 29 CFR1910.119(g). Apparently the demand for effective ways to implement PSM is on the rise. Basically the efficiency of standard implementation program process mostly depends on the systematic framework, which means that all the requirements must be considered, ensuring continuity and completing the implementation process. This paper presents a system to track the performance of training program based on compliance percentage. Furthermore, the system helps industry to manage and track information, documentations and required actions regarding the training program in systematic manner. Besides, it also provides a basis for gap analysis to be carried out for program improvement. Implementation of this system could serve as lagging indicator for improvement and ensure the competency of plant personnel as intended.